Implementasi Knowledge Management Menggunakan Model Big Data Untuk Media Sosial UMKM - Putri Permata Sari; Tulas Novalima; Eka Indah Wahyuni (CV. ITTC INDONESIA, 2025)
The purpose of this research is to examine the Implementation of Knowledge Management Using the Big data Model for MSME Social Media. With the rapid growth of data generated from interactions on social media, MSMEs are faced with the challenge of managing information effectively to improve competitiveness. This research uses a qualitative approach. This approach aims to explore the meaning, understanding, concepts, characteristics, symptoms, symbols, and descriptions of a phenomenon. This model describes the synergistic relationship between big data and KM and provides a framework for SMEs to use big data through KM. This framework includes four constructs, namely, strategic use of big data, knowledge-guided big data project planning, IT solutions for SMEs, and new knowledge products. Research results The implications for big data practices for different types of businesses may not be the same. Analysis of various business cases shows that successful SMEs should not ignore big data opportunities, and exploit big data by placing emphasis on KM, rather than on sophisticated IT techniques or the sheer magnitude of data, to generate knowledge products that are valuable to the competition.